Influence of Green Economic Development through Local Wisdom, Economic Potential, and Role of Dairy Cooperative in Pasuruan - Sutikno, Bambang; Hakim, Abdul; Batoro, Jati; Riniwati, Harsuko (International Review of Management and Marketing, 2018)
The purpose of this study was to analyze the influences of green economic development through local wisdom, economic potential, the role of dairy cooperatives in Pasuruan. This research sample number of 120 members of dairy cooperatives in Pasuruan. Sampling by using proportional random sampling. Research questionnaire used as an instrument of primary data collection. Data analysis technique used is the analysis generalized structured component analysis. The variables used in this study, includes the construction of a green economy development, local wisdom, economic potential, and the role of dairy cooperatives. The results showed green economic development is influence by local wisdom, economic potential, and the role of dairy cooperatives. Keywords: green economic development, local wisdom, economic potential, dairy cooperatives. JEL Classifications: O1, Q5